Validity of the DSM‐5 anxious distress specifier for major depressive disorder. Issue 1 (12th October 2018) - Zimmerman, Mark; Martin, Jacob; McGonigal, Patrick; Harris, Lauren; Kerr, Sophie; Balling, Caroline; Kiefer, Reina; Stanton, Kasey; Dalrymple, Kristy
Abstract : Background: DSM‐5 introduced the anxious distress specifier in recognition of the clinical significance of anxiety in depressed patients. Recent studies that supported the validity of the specifier did not use measures that were designed to assess the criteria of the specifier but instead approximated the DSM‐5 criteria from scales that were part of an existing data base. In the present report from the Rhode Island Methods to Improve Diagnostic Assessment and Services (MIDAS) project, we examined the validity of the specifier diagnosed with a semistructured interview. Methods: Two hundred sixty patients with a principal diagnosis of major depressive disorder were evaluated with semistructured diagnostic interviews. The patients were rated on clinician rating scales of depression, anxiety and irritability, and completed self‐report measures. Results: Approximately three‐quarters of the depressed patients met the criteria for the anxious distress specifier. Patients with anxious distress had a higher frequency of anxiety disorders, particularly panic disorder and generalized anxiety disorder, as well as higher scores on measures of anxiety, depression, and anger. The patients meeting the anxious distress subtype reported higher rates of drug use disorders, poorer functioning during the week before the evaluation, and poorer coping ability compared to the patients who did not meet the anxious distress specifier. Moreover, anxious distress was associated with poorer functioning and coping after controlling for the presence of an anxiety disorder. Conclusions: The results of the present study indicate that anxious distress is common in depressed patients and support the validity of the DSM‐5 anxious distress specifier.